2021
DOI: 10.3390/jpm11040301
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping Rare CFTR Mutations Reveal Functional Expression Defects Restored by TRIKAFTATM

Abstract: The rare Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) mutations, c.1826A > G (H609R) and c.3067_3072delATAGTG (I1023_V1024del), are associated with severe lung disease. Despite the existence of four CFTR targeted therapies, none have been approved for individuals with these mutations because the associated molecular defects were not known. In this study we examined the consequences of these mutations on protein processing and channel function in HEK293 cells. We found that, similar to F508del,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…These first-generation correctors have been followed by other compounds with improved efficacy due to their ability to target different CFTR domains or interfaces between them and thereby generate synergy in their modes of correction. The analysis of the current combination compounds has been described in the studies of Veit et al (2020) and Laselva et al (2021a) . The location of the CFTR2 mutants in different CFTR domains, together with the concept that the domains of CFTR fold cooperatively, suggests that these cooperative interactions require different pharmaco-chaperones to optimize their overall folding efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…These first-generation correctors have been followed by other compounds with improved efficacy due to their ability to target different CFTR domains or interfaces between them and thereby generate synergy in their modes of correction. The analysis of the current combination compounds has been described in the studies of Veit et al (2020) and Laselva et al (2021a) . The location of the CFTR2 mutants in different CFTR domains, together with the concept that the domains of CFTR fold cooperatively, suggests that these cooperative interactions require different pharmaco-chaperones to optimize their overall folding efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recently, the FDA approved as Trikafta/Kaftrio (US/Europe), the triple combination of two correctors, Elexacaftor (VX-445) and Tezacaftor, together with the potentiator Ivacaftor for patients bearing the F508del mutation at least on one allele [18]. Moreover, it has been demonstrated that Trikafta/Kaftrio was also effective on rarer class II mutations [19][20][21]. Based on in vitro cell-based studies, the FDA extended the list of CFTR mutations for which Trikafta/Kaftrio treatment could be clinically beneficial [22].…”
Section: Novel Therapies For Cfmentioning
confidence: 99%
“…A number of cell lines are being used to test the efficacy of CFTR modulator cocktails or gene therapies in rescuing the functional expression of F508del-CFTR. These models include Human Embryonic Kidney (HEK293), Fischer Rat Thyroid (FRT), and human bronchial epithelial cell lines (e.g., CFBE41o-) [21,43,44]. However, heterologous expression systems do not always predict CFTR modulators' efficacy in vitro [45,46].…”
Section: In Vivo and In Vitro Models For Cfmentioning
confidence: 99%
“…Novel drugs are improving mutant CFTR protein function, however many challenges still remain. There are considerable variations in drug responses and current drugs are not effective for all CF mutations ( Laselva et al, 2021 ). Multiple drug therapies are available for patients such as Kalydeco TM for patients >4-months with at least one G551D mutant allele, and the latest life-saving drug Trikafta TM approved for the majority of CF individuals with at least one F508del mutant allele in patients >6 years in the US and >12 years in Canada.…”
Section: Introductionmentioning
confidence: 99%